Tipologi Natas: Ruang Publik Tradisional di Wilayah Manggarai - Prakosa, Wahyu; Hendro Prabowo; Purnami, Wahyuni; Naingalis, Rosarius; Agung Wahyudi; Agus Suparman (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
Natas is a public space in Manggarai with various forms. The shape and orientation of natas are influenced by parrots. This is based on the shape, orientation, location of the compang and the presence of mbaru. This research uses a qualitative descriptive method with the steps: identifying the typology of shape and orientation of natas through field observations and interviews as well as indirect observation via Google Maps and Google Earth, analyzing the relationship between natas, compang and mbaru, creating patterns and formulating shapes and orientations based on natas typology. The results of this research reveal the diversity of natas shapes with a dominance of circular shapes and a tendency to follow parrots spatially. Natas is a place of social activities and traditional ceremonies that represent the unity of the Manggarai community.